Outpost Kelly : a tanker's story - Siewert, Jack R., 1924- (Fire ant books., 2006)
War at its most personal and lethal during the last four days of July 1952. In the second year of the Korean War, Jack Siewert commanded a platoon of five M-46 tanks. Temporarily assigned to provide fire support for an infantry battalion on the front, he eventually found himself in the midst of intense fighting for a relatively unknown and unimportant hill, code named Outpost Kelly. Those four days of battle against Chinese forces form the heart of this memoir, which is unique in its focus on the hill fighting that dominated two thirds of the Korean War. Trained to take advantage of his tanks &